The UbiBus Project: Using Context and Ubiquitous Computing to build Advanced Public Transportation Systems to Support Bus Passengers - Vieira, Vaninha; Salgado, Ana Carolina; Tedesco, Patricia; Times, Valeria; Ferraz, Carlos; Huzita, Elisa; Chaves, Ana Paula; Steinmacher, Igor (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2012: Anais do VIII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2012.14435, 2012)
Urban mobility is a problem that affects all cities. Providing real time information that can assist citizens on planning their trips by choosing times and itineraries more appropriate to their needs are essential on smart cities. Our project, named UbiBus, investigates how Computational Context and Ubiquitous Computing can be applied to Intelligent Transportation Systems to aid bus passengers mobility on cities, since dynamic real-time factors can affect transportation means. This paper describes the overall ideas concerning the UbiBus Project and presents some of the applications under development with their preliminary results.